Indirect restorations with digital workflow in hypomineralized permanent molars: A series of pediatric cases - Kelly Maria Silva Moreira; Fernanda Guzzo Tonial; José Carlos Pettorossi Imparato (Contemporary Pediatric Dentistry)
Molar incisor hypomineralization (MIH) is an enamel defect that presents significant challenges in clinical management due to its complexity and functional impact. This study evaluated the efficacy of indirect restorations in severely MIH-affected first permanent molars using digital technology and advanced restorative materials, including polymethyl methacrylate (PMMA), three-dimensional (3D) printed resin (Prizma Bio Crown, Makertech Labs, Tatuí, SP, Brazil), hybrid ceramic (Vita Enamic®, VITA Zahnfabrik, Bad Säckingen, Germany), and hybrid resin (Shofu Block HC, Shofu Inc., Kyoto, Japan). Molars from four pediatric patients were treated between August 2022 and August 2023 using a minimally invasive preparation approach, computer-aided design and manufacturing (CAD/CAM), and resin cementation techniques. The results demonstrated excellent marginal adaptation, high fracture resistance, improved aesthetics, reduced dental sensitivity, enhanced chewing function, and better oral hygiene maintenance over a follow-up period of 6 to 24 months. These findings suggest that indirect restorations are a suitable treatment option for severe MIH cases, with digital technology facilitating behavioral management and ensuring durable, high-quality restorations. Further studies comparing the performance of different restorative materials and evaluating cost-effectiveness are recommended to optimize clinical outcomes and practice.